Doubly thermo-responsive copolymers in ionic liquid. Issue 13 (2nd March 2016) - Nguyen, H. H.; El Ezzi, M.; Mingotaud, C.; Destarac, M.; Marty, J.-D.; Lauth-de Viguerie, N.
Abstract : A series of doubly thermo-responsive block copolymers made of n -butylacrylate and N -alkylacrylamides in [C2 mim][NTf2 ]. Abstract : We report the behaviour of thermoresponsive block copolymers of n -butyl acrylate and N -alkyl acrylamides in [C2 mim][NTf2 ]. Poly( N -isopropylacrylamide) exhibits an upper critical solution temperature in [C2 mim][NTf2 ] whereas poly( n -butyl acrylate) has a lower critical solution temperature. Consequently, these polymers exhibit double thermo-responsiveness correlated with the macromolecular structure. Moreover, a switching from micellar to reverse micellar structures was induced by a change in temperature. This property enables the development of reversible shuttles between ionic liquids and water.